Evaluation of the impacted maxillary canines position, determination of the possible indicators of the impaction difficulty, and the risk factors for adjacent teeth root resorption - Pajević, Tina; Vasović, Dina; Juloski, Jovana; Vučić, Ljiljana; Glišić, Branislav (Vojnosanitetski pregled, 2023)
Background/Aim. An impacted tooth is a tooth that could not erupt and take its place in the dental row. Impacted maxillary canines are a very frequent problem in orthodontic practices. They are the second most impacted teeth, right after the third molars. The aim of this cross-sectional study was to evaluate the two-dimensional and three-dimensional position of the impacted maxillary canines and make a descriptive study analysis of possible indicators of the impaction difficulty and risk factors for adjacent tooth root resorption. Methods. In this study, 94 subjects with 116 diagnosed maxillary canine impaction were included. The two-dimensional position of the impacted canines (IC) was evaluated on the panoramic projection of the cone beam computed tomography (CBCT) images. Canine position (CP) to the X, Y, and Z-axis was measured and scored using the novel classification system that incorporates three-dimensional information of CBCT imaging – the KPG index. Based on the KPG index value, impaction was defined as easy, moderate, difficult, and extremely difficult. In order to determine indicators of impaction difficulty and risk factors of root resorption of adjacent teeth, qualitative variables (gender, side of impaction, etc.) and quantitative variables [age, canine distance to the occlusal plane (OccP), etc.] were tested with multiple logistic regression. Results. The mean age of the subjects was 19.8 ± 5.2 years. The impactions were twice as prevalent in females compared to males. Most (71.4%) impactions were unilateral in palatal position of the canines. Adjacent root resorption was present in 27.3% of cases of impaction, and the central incisor was mostly affected. More than half of the impactions were of moderate level. In univariable analysis, canine distance to sagittal medial line (SML), angle between canine and SML, OccP, and first premolar, respectively, were significant in impaction difficulty prediction. Multivariable analysis showed that angle between canine and the first premolar could be a risk factor for adjacent root resorption. Conclusion. Most impacted maxillary canines were in the palatal position, with a KPG index value of moderate difficulty. Besides the position to the OccP and SML, angle between canine and the first premolar should be estimated, as a part of diagnostic procedures, to evaluate the risk of adjacent root resorption, prevent resorption, and decide on the treatment plan.
Keywords: cone-beam computed tomography; risk factors; tooth impacted; tooth resorption